Two-dimensional pseudo-random coupled map lattices system based on partitioned elementary cellular automata and its dynamic properties - Youheng DONG; Geng ZHAO; Yingjie MA (Tongxin xuebao)
To solve the weak chaos in the spatiotemporal chaotic system based on coupled map lattices under some control parameters and the un-uniformity of sequences generated by the coupled map lattices, a two-dimensional pseudo-random coupled map lattices (2D-PRCML) system was proposed.Firstly, the two-dimensional partitioned elementary cellular automata (2D-PECA) was designed to establish pseudo-random coupling.Secondly, iterative results of 2D-PECA were utilized to perturb the 2D-PRCML system.The chaotic behaviors of the proposed system, such as the bifurcation diagram, Kolmogorov-Sinai entropy, were investigated.Moreover, the uniformity of sequences generated by the 2D-PRCML system was discussed, and the correlation coefficients between any two sequences generated by different lattices were acquired.The analyses and tests indicate that the 2D-PRCML system exhibits stronger chaotic behavior.Furthermore, the sequence generated by the proposed system possesses better uniformity, randomness, and unpredictability.The outstanding properties of the 2D-PRCML system prove that it is more suitable for applying in cryptography and chaotic secure communication.